Anxiety Found in a Classroom with EMI Settings in Economics Education Department International Class at Universitas Negeri Padang - Dhuha, Rachmad Syamsu; Adnan, Aryuliva (Universitas Negeri Padang, 2024)
Anxieties in a classroom could come from different part, such as speaking, their ability to express opinion, material comprehension, understanding instructions from the teacher and also reading and writing comprehension. This research is intended to search and analyze the anxieties that the students have while in the EMI classroom in Economy Education Department International Class Universitas Negeri Padang. The instrument used for this research is a questionnaire given to the students. The outcome for the questionnaire given to the students will be divided into four categories: “Very Low” “Low” “Medium” “High”, calculated using the Likert Scale assessment method, and categorized using the Mean that have been calculated. The instrument used in this research is the Foreign Language Classroom Anxiety Scale or FLCAS, but with the use of different questions. The outcome shows several anxieties that the students had, such as being intimidated by other students with the mean of 3 which is in the category of low where 10 students or 76.9% of the class disagreed to questions, and also several anxieties outcome.